Autonomic and physiological stress responses in navy divers: the protective role of diving experience - Chen, Yu-Ju; Tzeng, Yuan-Sheng; Tang, Shih-En; Li, Chi-Rong; Wu, Shu-Yu; Huang, Kun-Lun (Frontiers in Physiology, 2025)
IntroductionDeep diving presents significant physiological stress, yet reliable indicators for monitoring autonomic and stress responses remain underdeveloped. This study examined how prior deep diving experience influences autonomic regulation and stress biomarkers during a simulated dive to a depth of 220 feet.MethodsTwenty-eight Navy divers (15 experienced, 13 novice) underwent psychological assessments (perceived stress, anxiety, fear) and salivary biomarker analysis (cortisol, amylase) pre- and post-dive. Heart rate variability (HRV), including linear (rMSSD, HF) and non-linear indices (SD1, SD1/SD2, sample entropy), was measured at four dive stages (pre-dive, bottom, decompression, and post-dive).ResultsAfter adjusting for age and perceived stress, experienced divers exhibited greater post-dive reductions in cortisol (p = 0.015) and amylase (p = 0.022). Additionally, after controlling for age, perceived stress, and respiratory rate, they also demonstrated significantly higher parasympathetic activity (p ≤ 0.001) and greater HRV complexity (sample entropy, p = 0.023) during decompression. No significant differences were found in self-reported psychological stress.DiscussionDiving experience facilitates enhanced autonomic control and stress adaptation. These findings support the use of real-time physiological monitoring and experience-based training protocols to mitigate risk during deep dives.